Preparation and Characterization of Gelatin and Chitosan Films. - Diop, Jeanette. (Tufts Archival Research Center, 2005)
This paper outlines the study of fabrication and characterization of gelatin and chitosan films with the goal of determining the optimal method of preparing these films in order to improve on their mechanical properties. Gelatin films were prepared by spin coating and casting on PDMS mold. Chitosan films were prepared by spin coating and drying known masses of samples in the fume hood or the oven. Films were stored in a vacuum chamber when not being tested. Each film was tensile tested for its Modulus of Elasticity, Tensile Strength, Yield Strength, and Elongation at Break. Tensile properties of films are affected by various innate properties of the film such as moisture content of the films, physicochemical properties of the films, humidity of the atmosphere during testing. The results of this project indicated that gelatin films prepared by casting were better suited for tensile testing. In order to minimize atmospheric effects, films must be stored in a vacuum box or dessicator until testing. Chitosan films that are washed with sodium hydroxide solution after drying were less susceptible to humidity; chitosan films prepared with acetic acid tend to be easier to handle during film preparation and testing.